Panic disorder: Epidemiology, disability, and treatment gap from nationally representative general population of India - Pavithra Jayasankar; Suhas Satish; Hari Hara Suchandra; Narayana Manjunatha; Girish N. Rao; Gopalkrishna Gururaj; Mathew Varghese; Vivek Benegal; NMHS National Collaborators Group (Indian Journal of Psychiatry)
Introduction: Panic disorder (PD) is one of the most common and debilitating anxiety disorder. Individuals with PD seek frequent healthcare and emergency services leading to frequent work absenteeism and economic burden. However, its prevalence patterns in the Indian context are poorly understood. Hence, this article discusses the epidemiology, disability, and treatment gap from India's National Mental Health Survey 2016. Materials and Methods: National Mental Health Survey 2016 was a nationally representative epidemiological survey of adult respondents from 12 states of India. Mini International Neuropsychiatric Interview 6.0.0 is used to diagnose psychiatric disorders. Sheehan disability scale was used to assess the disability. The current weighted prevalence of PD was estimated. Association between PD and its sociodemographic correlates was done using Firth penalized logistic regression. The treatment gap and disability in PD were also calculated. Results: The lifetime and current weighted prevalence of PD was 0.5% (95% confidence interval 0.49-0.52) and 0.3% (95% confidence interval 0.28-0.41), respectively. The male gender and unemployed have significantly lesser odds with current PD. The elderly, Urban metro, and the married/separated group have significantly higher odds with current PD. The most common comorbid psychiatric disorder is agoraphobia (42.3%) and depression (30.9%) followed by Generalized Anxiety Disorder (10%). Among respondents with current PD in the past 1 month across three domains, around 80% had a disability of any severity and 20%-25% had marked disability. The overall treatment gap of current PD is 71.7%. Conclusion: It is the first study reporting prevalence from a nationally representative sample from the general population of India. The survey has shed light on the epidemiology and the challenges faced by those with PD which emphasizes the urgency of bridging the treatment gap. These findings are paramount to the development of more inclusive and effective mental health policies and interventions to tackle the current burden due to PD.